The Presence of Seals on Dressel 20 Amphorae in Londinium–Camulodunum and Mogontiacum: a Quantitative-comparative Analysis and its Derived Trade Dynamics - Remesal Rodríguez, José; Bermúdez Lorenzo, Juan Manuel (Gerión. Revista de Historia Antigua, 2021)
This paper aims to compare the epigraphy on amphorae Dressel 20 (stamps) of two points of the Roman Empire with a parallel chronology: Mogontiacum (Mainz) and Londinium (London), with Camulodunum. For this purpose, we will take in account the information contained in the database CEIPAC of amphorae epigraphy. We have as objective to delimit the dynamics of oil arrival from Baetica and put it in relation with the army or civil consumption of these towns.
Keywords: Amphorae Stamps; Dressel 20; Trade History of the Limes